2005
DOI: 10.1002/ana.20692
|View full text |Cite
|
Sign up to set email alerts
|

Altered plasticity of the human motor cortex in Parkinson's disease

Abstract: Interventional paired associative stimulation (IPAS) to the contralateral peripheral nerve and cerebral cortex can enhance the primary motor cortex (M1) excitability with two synchronously arriving inputs. This study investigated whether dopamine contributed to the associative long-term potentiation-like effect in the M1 in Parkinson's disease (PD) patients. Eighteen right-handed PD patients and 11 right-handed age-matched healthy volunteers were studied. All patients were studied after 12 hours off medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
116
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(134 citation statements)
references
References 86 publications
14
116
1
Order By: Relevance
“…The absence of the PAS response on the more affected side is in line with previous studies in patients with more advanced PD, 18,19 who show decreased response to PAS in the "off " state that normalizes with L-dopa. 18 The reduced response to PAS is explained as being secondary to abnormal basal ganglia output 20 or to result from reduced dopamine at the cortical level.…”
Section: Resultssupporting
confidence: 91%
“…The absence of the PAS response on the more affected side is in line with previous studies in patients with more advanced PD, 18,19 who show decreased response to PAS in the "off " state that normalizes with L-dopa. 18 The reduced response to PAS is explained as being secondary to abnormal basal ganglia output 20 or to result from reduced dopamine at the cortical level.…”
Section: Resultssupporting
confidence: 91%
“…Impaired PAS-induced LTP-like plasticity is typically observed in disorders associated with a dysfunctional dopaminergic system such as Parkinson's disease (Morgante et al, 2006;Ueki et al, 2006;Schwingenschuh et al, 2010) or schizophrenia (Frantseva et al, 2008), or a deficient central cholinergic system such as Alzheimer's disease (Battaglia et al, 2007), whereas exaggerated PASinduced LTP-like plasticity can be observed in states of increased endogenous central cholinergic tone such as dystonia (Quartarone et al, 2003(Quartarone et al, , 2008Weise et al, 2006;Schwingenschuh et al, 2010).…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Animal studies have revealed an inverted U-shaped dose-response curve of dopamine on cognition (Williams and Goldman-Rakic, 1995;Granon et al, 2000;Seamans and Yang, 2004). Interestingly, PAS-induced plasticity is absent in ParkinsonŠˆs disease patients off medication, but restituted by dopaminergic agents (Ueki et al, 2006). However, only dosage dependency of dopamine on tDCS-induced plasticity (Monte-Silva et al, 2010), but not associative plasticity, has been explored so far.…”
Section: Introductionmentioning
confidence: 99%